The prevalence of malnutrition and obesity in patients with head and neck cancer - Przybyszewska, Justyna; Sinkiewicz, Anna; Winiarski, Piotr (Journal of Education, Health and Sport, 2017)
Introduction Tumor development in head and neck area leads to the occurrence of severe pain and disorders of vital signs, such as breathing and eating. In addition, head and neck cancer often result in: loss of appetite, malabsorption and metabolic disorders, thereby contributing to the development or worse of malnutrition. Objective The aim of this study was to evaluate the prevalence of abnormalities in nutritional status, including malnutrition and obesity in patients with head and neck cancer. Material and methods Study group consisted of 48 patients (32 men and 16 women) admitted for treatment at the Department of Otolaryngology and Laryngological Oncology of Subdivision Jaw Surgery, University Hospital No. 2. Dr. John Biziela in Bzdgoszcz. Age of the subjects ranged from 36 to 81 years (mean 59.59 ± 10.40 years). Nutritional status of patients admitted to the study were evaluated based on the results of anthropometric indicators. Results In our study, obesity, determined on the basis of individual values of body mass index (BMI) was reported in 9.4% of men and 6.2% of women. A much higher percentage (50.0%) obese patients were observed when interpreted of the percentage of fat in the body. Additionally, showed that for more than half of the total study group (including 40.6% of men and 81.2% women) were characteristic abdominal obesity. Low values of AMC, suggesting deficiency of reserves of protein in the body, was observed in every third patient, including 28.1% of men and 37.5% women. Conclusion Results of this study showed that there were irregularities in the nutritional status of patients with head and neck cancer. Described abnormalities were associated mainly with a high percentage of protein malnutrition and the prevalence of excessive body fatness.